Hydraulic composition
Patent Information
- Application Number
- JP2022098280
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-06-17
- Publication Date
- 2025-03-13
- Estimated Expiration
- 2042-06-17
AI Technical Summary
Existing geopolymer compositions using strong alkaline irritants face issues with reduced fluidity retention and accelerated curing, leading to impaired workability and shortened pot life.
A hydraulic composition comprising fine aggregate, metasilicate, alumina-silica fine powder, potassium carbonate, and water, which improves fluidity retention and strength of the cured product by controlling the pH and suppressing rapid hydration product formation.
The composition achieves excellent fluidity retention and strength development, contributing to sustainable development goals by effectively utilizing industrial by-products and reducing emissions.
Smart Images

Figure 00000009_0000
Abstract
Description
Technical Field
[0001] The present invention relates to a hydraulic composition and a method for producing a cured body.
Background Art
[0002] In recent years, for the realization of SDGs, infrastructure development considering the environment from the ESG perspective has been aimed at, and technological development related to an environmentally harmonious hydraulic composition with reduced cement that emits CO2 during the firing of calcium carbonate has been progressing.
[0003] As an example, a hydraulic composition called geopolymers, which cures blast furnace slag fine powder containing silicates such as aluminum silicate using an alkaline solution, has attracted attention.
[0004] Geopolymers cure by the dissolution of aluminum silicate in alkali and the formation of hydration products. Therefore, the more a strongly basic alkali stimulant such as sodium hydroxide or potassium hydroxide is used in combination, the better the strength development property is shown.
[0005] Patent Document 1 discloses using a mixture of sodium silicate and sodium carbonate as a curing accelerator for geopolymers using alumina-silica fine powder.
[0006] Patent Document 2 discloses a bicarbonate-based curing agent in a silicate-based earth stabilizing chemical solution containing, in a predetermined ratio, a component a: sodium bicarbonate, a component b: potassium bicarbonate, a component c: at least one selected from the group consisting of powdery naphthalenesulfonic acid-based compounds, ligninsulfonic acid-based compounds, oxycarboxylic acid-based compounds, and melaminesulfonic acid-based compounds, and a component d: an alkali metal carbonate.
[0007] Non-Patent Document 1 discloses the definition, materials, mechanisms, problems, and possibilities of geopolymers. Non-patent document 2 discloses a one-component geopolymer comprising alumina silica fine powder, a powdered alkaline compound, and aggregate, without the use of an alkaline solution. [Prior art documents] [Patent Documents]
[0008] [Patent Document 1] U.S. Patent Application Publication No. 2015 / 0321954 [Patent Document 2] Japanese Patent Publication No. 2002-88365 [Non-patent literature]
[0009] [Non-Patent Document 1] Concrete Engineering, Vol. 56, No. 5, pp. 409-414, The Japan Concrete Institute, published May 2018. [Non-Patent Document 2] Cement and Concrete Research, Vol. 103, pp. 21-34, Elsevier BV, November 2017. [Overview of the project] [Problems that the invention aims to solve]
[0010] However, when using a geopolymer made from metasilicate and alumina silica fine powder in combination with a strongly basic alkaline stimulant, there was a problem in that the fluidity retention decreased, for example, curing was significantly accelerated, shortening the pot life and impairing workability.
[0011] This invention provides a geopolymer-type hydraulic composition that exhibits excellent fluid retention and strength in the cured product. [Means for solving the problem]
[0012] The present invention relates to a hydraulic composition containing (A) fine aggregate [hereinafter referred to as component (A)], (B) metasilicate [hereinafter referred to as component (B)], (C) alumina silica fine powder [hereinafter referred to as component (C)], (D) potassium carbonate [hereinafter referred to as component (D)], and (E) water [hereinafter referred to as component (E)].
[0013] Furthermore, the present invention relates to a method for producing a hardened body by curing the hydraulic composition of the present invention. [Effects of the Invention]
[0014] According to the present invention, a geopolymer-type hydraulic composition is provided that exhibits excellent fluid retention and strength of the cured product. Because this invention contributes to the effective utilization of industrial by-products and waste, and to the reduction of CO2 emissions, it is considered that this technology could contribute to SDGs such as No. 7, 9, 11, 12, and 13, which have been advocated in recent years for the realization of a sustainable society. [Brief explanation of the drawing]
[0015] [Figure 1] Graph showing the results of the examples and comparative examples. [Modes for carrying out the invention]
[0016] The inventors have found that by adding potassium carbonate to a hydraulic composition comprising fine aggregate, metasilicate, alumina silica fine powder, and water, the fluidity retention of the hydraulic composition is improved, ensuring, for example, an appropriate pot life as a hydraulic slurry, and that the hardened body of such a hydraulic composition exhibits sufficient strength. The reason for these effects is not entirely clear, but it is speculated to be as follows. As described above, the geopolymers are formed by the alkaline dissolution of aluminosilicate and the subsequent formation of hydrated products. Representative hydrated products contributing to strength development include complexes of calcium, aluminum, and silicon oxides called C-S(A)-H. This hydrated product is known to grow rapidly under high pH and in an environment where calcium ions are dissolved. In the present invention, potassium carbonate suppresses the decrease in fluidity associated with the rapid formation of C-S(A)-H due to the lower pH of its aqueous solution compared to general alkaline stimulants, and solidifies (cures) excess calcium ions derived from alumina-silica fine powder as calcium carbonate, thereby achieving both fluidity retention as a hydraulic slurry and strength development of the cured body.
[0017] <Hydraulic composition> The hydraulic composition of the present invention contains (A) fine aggregate, (B) metasilicate, (C) alumina-silica fine powder, (D) potassium carbonate, and (E) water.
[0018] (Component (A) is a fine aggregate. Component (A) may be natural sand or artificial sand. Examples of natural sand include river sand, land sand, mountain sand, sea sand, lime sand, silica sand, chromite sand, zircon sand, olivine sand, alumina sand, natural lightweight fine aggregate, and crushed sand thereof. Examples of artificial sand include blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, recycled fine aggregate, synthetic mullite sand, SiO2-based artificial sand with SiO2 as the main component, Al2O3-based artificial sand with Al2O3 as the main component, SiO2 / Al2O3-based artificial sand, SiO2 / MgO-based artificial sand, SiO2 / Al2O3 / ZrO2-based artificial sand, SiO2 / Al2O3 / Fe2O3-based artificial sand, etc. Here, the main component refers to the most abundant component among the components contained in the sand. These may be used alone or in combination of two or more.
[0019] (A) The components are preferably one or more selected from river sand, land sand, mountain sand, sea sand, lime sand, silica sand, blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, natural lightweight fine aggregate, and recycled fine aggregate. These may be crushed sand.
[0020] From the viewpoint of the workability of the hydraulic composition (hydraulic slurry), the degree of amorphousness of the fine aggregate is preferably 30% or less, more preferably 20% or less, even more preferably 10% or less, and even more preferably 5% or less. There is no lower limit to the degree of amorphization of the fine aggregate, but for example, it may be 0% or more, or 1% or more.
[0021] (A) There are various methods for controlling the degree of amorphousness of component (A), but generally it is preferable to use a manufacturing method that rapidly cools the molten material. For example, there are methods of melting the raw material and rapidly cooling it by blowing it with air, or processing it in a flame and rapidly cooling it. In any case, the cooling method can be appropriately selected at various rates depending on the material and particle size. It is also possible to make amorphous material that has already crystallized by heat treatment and cooling treatment. Among these, the flame melting method, in which heating and cooling can be easily controlled, is preferred.
[0022] The degree of amorphousness of component (A) can be determined by the X-ray diffraction method shown below. Fine aggregate is crushed in a mortar and pressed onto the X-ray glass holder of a powder X-ray diffractometer for measurement. The powder X-ray diffractometer used is a MultiFlex manufactured by Rigaku Denki Co., Ltd. (light source: CuKα rays, tube voltage: 40kV, tube current: 40mA), and measurements are performed in the range of 2θ = 5 to 90° with a scanning interval of 0.01°, a scanning speed of 2° / min, and slits DS1, SS1, RS 0.3mm. In the range of 2θ = 10° to 50°, the X-ray intensities on the low and high angle sides are connected by straight lines, and the area below the line is defined as the background. The degree of crystallinity is determined using the software attached to the instrument, and subtracted from 100 to obtain the degree of amorphousness. Specifically, for the area above the background, amorphous peaks (halos) and each crystalline component are separated by curve fitting, the area of each is determined, and the degree of amorphousness (%) is calculated using the following formula. Amorphization (%) = Area of halo / (Area of crystalline components + Area of halo) × 100
[0023] Component (A) is preferably spherical from the viewpoint of improving the flow retention of the hydraulic composition. Here, spherical in this embodiment means having a round shape like a ball, and more specifically, it means having a sphericity of 0.80 or higher, more preferably 0.85 or higher, even more preferably 0.90 or higher, even more preferably 0.95 or higher, and even more preferably 0.97 or higher. It is preferable from the viewpoint of flow retention if the sphericity of the fine aggregate in this embodiment is above the above lower limit. Furthermore, it is also preferable from the viewpoint that the surface becomes smoother if the sphericity of the fine aggregate in this embodiment is above the above lower limit. Furthermore, the upper limit for sphericity is specifically 1 or less.
[0024] (A) The sphericity of component (A) is determined by image analysis of the particle image (photograph) obtained using an optical microscope or digital scope (e.g., Keyence VH-8000), thereby determining the area of the particle projection cross-section and the perimeter of said cross-section, and then [Area of particle projection cross-section (mm²)] 2 The value can be calculated by dividing the circumference of a perfect circle with the same area (mm) by the perimeter of the particle projection cross-section (mm), and then averaging the obtained values for any 50 particles.
[0025] (A) The average particle size of component (A) is preferably 0.1 mm or more, more preferably 0.5 mm or more, and more preferably 5.0 mm or less, more preferably 2.0 mm or less, and even more preferably 1.0 mm or less, from the viewpoint of workability of the hydraulic composition. The average particle size of component (A) can be measured by the following method.
[0026] (Method for measuring average particle size) If the sphericity of the particle from the particle projection cross-section is 1, the diameter (mm) is measured. On the other hand, if the sphericity is < 1, the major axis diameter (mm) and minor axis diameter (mm) of randomly oriented particles are measured, and (major axis diameter + minor axis diameter) / 2 is calculated. For any 100 particles, the obtained values are averaged to obtain the average particle diameter (mm). The major axis diameter and minor axis diameter are defined as follows: When a particle is stabilized on a plane and its projection image onto the plane is sandwiched between two parallel lines, the width of the particle at which the distance between the parallel lines is minimized is called the minor axis diameter. On the other hand, the distance when the particle is sandwiched between two parallel lines perpendicular to these parallel lines is called the major axis diameter. The major and minor axis diameters of a particle can be determined by taking an image (photograph) of the particle using an optical microscope or digital scope (for example, Keyence VH-8000 model) and performing image analysis on the obtained image.
[0027] The hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (A) in amounts of, for example, 10 parts by mass or more, more 20 parts by mass or more, more 30 parts by mass or more, from the viewpoint of strength development of the hardened body of the hydraulic composition, and 90 parts by mass or less, more 80 parts by mass or less, more 70 parts by mass or less, from the viewpoint of workability of the hydraulic composition.
[0028] Next, we will explain the metasilicate of component (B). Examples of metasilicates include concentrated aqueous solutions of sodium metasilicate, so-called water glass (e.g., composition formula Na2SiO3·nH2O, n=1.3~4.0). Examples of solid metasilicate hydrates include sodium metasilicate pentahydrate, sodium metasilicate nonahydrate, potassium metasilicate pentahydrate, potassium metasilicate nonahydrate, and magnesium metasilicate pentahydrate. Component (B) is preferably one or more selected from water glass, sodium metasilicate pentahydrate, and sodium metasilicate nonahydrate.
[0029] The hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (B) in amounts of, for example, 0.1 parts by mass or more, further 0.5 parts by mass or more, further 1.0 part by mass or more, and 20 parts by mass or less, further 15 parts by mass or less, and further 10 parts by mass or less, from the viewpoint of strength development of the hardened body of the hydraulic composition.
[0030] From the viewpoint of the strength development of the hardened body of the hydraulic composition of the present invention, component (B) may be contained in an amount of, for example, 0.05 parts by mass or more, preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1 part by mass or more, even more preferably 2 parts by mass or more, and for example, 10 parts by mass or less, preferably 8 parts by mass or less, and more preferably 6 parts by mass or less, per 100 parts by mass of component (A).
[0031] Next, we will explain the alumina silica fine powder, which is component (C). (C) Examples of alumina silica fine powder include fine powder containing aluminosilicate (xM2O·yAl2O3·zSiO2·nH2O, where M is an alkali metal). Component (C) has the effect of eluting cations such as aluminum and silicon upon contact with alkaline compounds and / or aqueous solutions thereof, and acting as a source of these cations.
[0032] (C) The molar ratio of alumina (Al2O3) to silica (SiO2) of component (C) may be, from the viewpoint of strength development of the hardened product of the hydraulic composition, for example, 0.05 or more, more specifically 0.10 or more, and 1.00 or less, and more specifically 0.50 or less in terms of alumina / silica.
[0033] (C) Suitable examples of alumina silica fine powder include: 1) industrial waste and by-products such as blast furnace slag fine powder, fly ash, clinker ash, fluidized bed coal ash, municipal solid waste incineration ash molten slag fine powder, red mud, and sewage sludge incineration ash molten slag fine powder; 2) natural aluminosilicate minerals such as metakaolin and clay and their ceramics; and 3) volcanic ash. Of these, the industrial waste described in 1) above is particularly suitable because, compared to the other components, it has no restrictions on its origin and contributes to the effective utilization of industrial waste resources.
[0034] (C) Component may be one or more selected from blast furnace slag fine powder, fly ash, metakaolin, rice husk incineration ash, coconut husk incineration ash, municipal solid waste incineration ash, and sewage sludge incineration ash. (C) Component may preferably be one or more selected from blast furnace slag fine powder and fly ash.
[0035] In the present invention, two or more types of component (C) can be used. When two or more types of component (C) are used in the present invention, for example, when two or more types selected from blast furnace slag fine powder, fly ash, metakaolin, rice husk incineration ash, coconut husk incineration ash, municipal solid waste incineration ash, and sewage sludge incineration ash are used as component (C), it is preferable that the hydraulic composition of the present invention contains blast furnace slag fine powder as component (C) from the viewpoint of strength development of the hardened body of the hydraulic composition.
[0036] When the hydraulic composition of the present invention contains two or more components (C), and contains blast furnace slag fine powder as component (C), from the viewpoint of strength development of the hardened body of the hydraulic composition, the proportion of blast furnace slag fine powder in component (C) is, for example, 10 parts by mass or more, preferably 20 parts by mass or more, more preferably 30 parts by mass or more, and for example 90 parts by mass or less, preferably 80 parts by mass or less, and more preferably 70 parts by mass or less, per 100 parts by mass of component (C). The hydraulic composition of the present invention preferably contains, as component (C), (C1) blast furnace slag fine powder and (C2) one or more selected from fly ash, metakaolin, rice husk incineration ash, coconut husk incineration ash, municipal solid waste incineration ash, and sewage sludge incineration ash. (C2) is preferably fly ash.
[0037] Blast furnace slag powder is a by-product of iron refining in a blast furnace, and its main components are calcium oxide (CaO), silica (SiO2), and alumina (Al2O3). Its specifications are defined in JIS A 6206. In this invention, it is preferable to use blast furnace slag powder with a CaO content in the range of 30% by mass to 60% by mass. Fly ash is mainly composed of silica (SiO2) and alumina (Al2O3), and is classified into four types (I to IV) in JIS A 6201 based on particle size and flow value. JIS types I and II, which have fine particle size and high reactivity, are suitable. The CaO content in the fly ash may be 10.1% by mass or less.
[0038] (C) Component is the Blaine specific surface area (cm²). 2 The ratio ( / g) is, from the viewpoint of strength development of the hardened hydraulic slurry, for example, 1,500 or more, preferably 2,000 or more, more preferably 2,500 or more, even more preferably 3,000 or more, and even more preferably 3,500 or more. From the viewpoint of handlingability of the powdered hydraulic composition, it is, for example, 8,000 or less, preferably 7,500 or less, more preferably 7,000 or less, even more preferably 6,500 or less, and even more preferably 6,000 or less. The Blaine specific surface area of component (C) is measured and calculated using a Blaine air permeability device specified in JIS R 5201.
[0039] The hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (C) in amounts of, for example, 5 parts by mass or more, further 10 parts by mass or more, further 20 parts by mass or more, and 60 parts by mass or less, further 50 parts by mass or less, and further 40 parts by mass or less, from the viewpoint of strength development of the hardened body of the hydraulic composition.
[0040] Component (D) is potassium carbonate. Component (D) may function as an alkaline stimulant. The hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (D) in amounts of, for example, 0.1 parts by mass or more, further 0.5 parts by mass or more, further 1.0 part by mass or more, and 15 parts by mass or less, further 10 parts by mass or less, and further 5 parts by mass or less, from the viewpoint of strength development of the hardened body of the hydraulic composition.
[0041] From the viewpoint of the strength development of the hardened body of the hydraulic composition of the present invention, the content of component (D) may be, for example, 20 parts by mass or more, further 40 parts by mass or more, further 60 parts by mass or more, and 250 parts by mass or less, further 230 parts by mass or less, and further 210 parts by mass or less, per 100 parts by mass of component (B).
[0042] Component (E) is water. The hydraulic composition of the present invention may contain, per 100 parts by mass of the composition, component (E) in amounts of, for example, 5.0 parts by mass or more, more specifically 7.5 parts by mass or more, more specifically 10.0 parts by mass or more, from the viewpoint of the workability of the hydraulic composition, and 40.0 parts by mass or less, more specifically 30.0 parts by mass or less, more specifically 20.0 parts by mass or less, from the viewpoint of the strength development of the hardened body of the hydraulic composition.
[0043] The hydraulic composition of the present invention may contain any component other than components (A), (B), (C), (D), and (E). Examples of optional components include water-reducing agents, air-entraining agents, fluidizing agents, hardening accelerators (alkaline stimulants), defoaming agents, rapid setting agents, shrinkage reducing agents, hardening retarders, and rust inhibitors. The hydraulic composition of the present invention may contain one or more of these optional components.
[0044] The hydraulic composition of the present invention may optionally contain cement, but care must be taken with its content as cement affects the initial hardening rate. Furthermore, from the viewpoint of providing a hydraulic composition with reduced cement content, a lower cement content is preferable. The hydraulic composition of the present invention may optionally contain cement, and the cement content may be less than 30 parts by mass, more preferably 20 parts by mass or less, more preferably 10 parts by mass or less, or more preferably 1 part by mass or less, per 100 parts by mass of component (C), and may also contain 0 parts by mass, i.e., no cement at all. Here, examples of cement include Portland cement, white Portland cement, blended cement, eco-cement, alumina cement, ultrafast-setting cement, grout cement, oil well cement, etc. The content of Portland cement in the hydraulic composition of the present invention may be within the above range relative to component (C).
[0045] The hydraulic composition of the present invention may be a hydraulic composition comprising components (A), (B), (C), (D), and (E). In this case, the amount of each component can be selected from the content range indicated for each component, with the total amount of components in the composition being 100 parts by mass. The hydraulic composition of the present invention may be a composition for geopolymers. The hydraulic composition of the present invention can be produced by mixing components (A) to (E). There are no particular limitations on the mixing order of each component.
[0046] <Method for manufacturing a hardened body> The present invention relates to a method for producing a hardened body, which involves curing the hydraulic composition of the present invention. In the present invention, the curing of the hydraulic composition can be carried out under general conditions for obtaining a cured geopolymer. In the present invention, the curing temperature can be, for example, 20°C or higher, further 30°C or higher, further 40°C or higher, and 80°C or lower, and further 70°C or lower. In addition, in step (II), the curing time can be, for example, 1 hour or more and 28 days or less. [Examples]
[0047] The components used in the examples and comparative examples are shown below. (A) Composition: Mountain sand (from Joyo, Kyoto City, surface dry specific gravity 2.54, coarseness 2.73, amorphity 1.1%, sphericity 0.86, average particle size 0.6 mm, in an oven-dry state) (B) Ingredients: Sodium metasilicate no. hydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (C) Component (C-1): Blast furnace slag fine powder (Brain specific surface area: 4,200 cm²) 2 ( / g, alumina / silica molar ratio = 0.25) (C-2): Fly ash (JIS Class II, Blaine specific surface area: 3,500 cm²) 2 ( / g, alumina / silica molar ratio = 0.26) (D) Component (D-1): Potassium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (D') component (comparative component of (D) component) (D'-1): Sodium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (D'-2): Potassium hydroxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (D'-3): Sodium carbonate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (E) Ingredients: Tap water (Wakayama City tap water)
[0048] <Examples and Comparative Examples> (1) Preparation of hydraulic compositions and their hardened bodies Components (A), (B), (C), (D), (D'), and (E) were added in the parts by mass shown in Table 1 to a Hobart mixer as described in JIS R 5201, and mixed at 140 rpm for 180 seconds to prepare the hydraulic compositions of the examples and comparative examples.
[0049] (2) Evaluation of usable time The mortar flow immediately after preparation and the mortar flow 30 minutes after preparation of the hydraulic composition prepared as described in (1) were measured and recorded in accordance with JIS R 5201. The mortar flow 30 minutes after preparation was measured after covering the prepared hydraulic composition with a damp towel, letting it stand in the dark at 20°C for 30 minutes, and then re-stirring it with the above mixer at 140 rpm for 10 seconds. The flow retention rate after 30 minutes was calculated based on the following formula and used as an indicator of pot life. The larger this value, the better the processability after a certain period of time and the longer the pot life can be evaluated. The results are shown in Table 1. Flow retention rate (%) = [F0 / F30] × 100 F0: Mortar flow immediately after preparation F30: Mortar flow 30 minutes after preparation
[0050] (3) Evaluation of strength Using the hydraulic composition prepared as described in (1) immediately after preparation, φ5 × 10 cm mortar specimens were prepared in accordance with JSCE-F 506, sealed and cured at 20°C for 7 days, then demolded, and a compressive strength test was conducted in accordance with JSCE-G 505, with the uniaxial compressive strength (N / mm²) being the average value of n=2. 2 ) was recorded. The results are shown in Table 1.
[0051] [Table 1]
[0052] The results from Table 1 are summarized in Figure 1. As can be seen from Table 1 and Figure 1, Examples 1-2 showed superior fluidity retention and strength development compared to Comparative Examples 1-4. It can be seen that even when using components that can function as alkaline stimulants, as in Comparative Examples 2-4, it is not possible to achieve both fluidity retention and strength as with potassium carbonate component (D) of the present invention. This is thought to be due to the effect obtained by curing excess calcium ions derived from alumina silica fine powder into calcium carbonate while suppressing the decrease in pot life associated with the rapid formation of CS(A)-H, as mentioned above, by the lower pH of the aqueous solution of potassium carbonate component (D) used in the present invention compared to component (D') used for comparison.
Claims
1. A hydraulic composition comprising (A) fine aggregate (hereinafter referred to as component (A)), (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder (hereinafter referred to as component (C)), (D) potassium carbonate (hereinafter referred to as component (D)) and (E) water (hereinafter referred to as component (E)).
2. 2. The hydraulic composition according to claim 1, wherein the component (A) is at least one selected from the group consisting of river sand, land sand, mountain sand, sea sand, lime sand, silica sand, blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, natural lightweight fine aggregate, and recycled fine aggregate.
3. 3. The hydraulic composition according to claim 1 or 2, wherein the component (C) is at least one selected from the group consisting of ground granulated blast furnace slag, fly ash, metakaolin, rice husk incineration ash, coconut shell incineration ash, municipal waste incineration ash, and sewage sludge incineration ash.
4. 3. The hydraulic composition according to claim 1, wherein the component (B) is at least one selected from the group consisting of water glass, sodium metasilicate pentahydrate and sodium metasilicate nonahydrate.
5. 3. The hydraulic composition according to claim 1 or 2, which optionally contains cement, and the content of the cement is less than 30 parts by mass per 100 parts by mass of the component (C).
6. 3. The hydraulic composition according to claim 1, wherein the content of the component (D) is 50 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the component (B).
7. A method for producing a hardened body, comprising curing a hydraulic composition containing (A) fine aggregate (hereinafter referred to as component (A)), (B) metasilicate (hereinafter referred to as component (B)), (C) alumina-silica fine powder (hereinafter referred to as component (C)), (D) potassium carbonate (hereinafter referred to as component (D)) and (E) water (hereinafter referred to as component (E)) to obtain a hardened body.
8. A method for producing a hardened body as described in claim 7, wherein component (A) is one or more selected from river sand, land sand, mountain sand, sea sand, lime sand, silica sand, blast furnace slag fine aggregate, ferronickel slag fine aggregate, artificial lightweight fine aggregate, natural lightweight fine aggregate, and recycled fine aggregate.
9. A method for producing a hardened body as described in claim 7, wherein component (C) is one or more selected from the group consisting of blast furnace slag powder, fly ash, metakaolin, rice husk incineration ash, coconut shell incineration ash, municipal waste incineration ash, and sewage sludge incineration ash.
10. A method for producing a hardened body as described in claim 7, wherein component (B) is one or more selected from water glass, sodium metasilicate pentahydrate, and sodium metasilicate nonahydrate.
11. A method for producing a hardened body as described in claim 7, optionally containing cement, wherein the cement content is less than 30 parts by mass per 100 parts by mass of component (C).
12. A method for producing a hardened body as described in claim 7, wherein the content of the (D) component is 50 parts by mass or more and 300 parts by mass or less per 100 parts by mass of the (B) component.
13. The method for producing a hardened product according to any one of claims 7 to 12, wherein the hydraulic composition is cured at 20°C or higher to obtain a hardened product.